Probabilistic acute risk assessment of cumulative exposure to organophosphorus and carbamate pesticides from dietary vegetables and fruits in Shanghai populations. Issue 5 (4th May 2017) - Li, Fan; Yuan, Yaqun; Meng, Pai; Wu, Min; Li, Shuguang; Chen, Bo
ABSTRACT: Organophosphorus pesticides (OPs) and carbamate pesticides (CPs) are among the most widely used pesticides in China, playing a major role in protecting agricultural commodities. In this study, we determined the cumulative acute exposure to OPs and CPs of Shanghai residents from vegetables and fruits (VFs). The food consumption data were obtained from the Shanghai Food Consumption Survey (SHFCS) of 2012–14 including a total of 1973 participants aged 2–90 years. The pesticide residue data were obtained from the Shanghai monitoring programme during 2008–11 with 34 organophosphates and 11 carbamates analysed in a total of 5335 samples of VFs. A probabilistic approach was performed as recommended by the EFSA, using the optimistic model with non-detects set as zero and with processing factors (PFs) being used and the pessimistic model with non-detects replaced by limit of detection (LOD) and without PFs. We used the relative potency factor (RPF) method to normalise the various pesticides to the index compound (IC) of methamidophos and chlorpyrifos separately. Only in the pessimistic model using methamidophos as the IC was there was small risk of exposure exceeding the ARfD (3 µg kg – 1 bw day – 1 ) in the populations of preschool children (0.029%), school-age children (0.022%) and adults (0.002%). There were no risk of exposure exceeding the ARfD of methamidophos in the optimistic model and of chlorpyrifos (100 µg kg – 1 bw day – 1 ) in both optimistic and pessimistic models in all three populations. Considering the Chinese habits of overwhelmingly eating processed food (vegetables being cooked, and fruits being washed or peeled), we conclude that little acute risk was found for the exposure to VF-sourced OPs and CPs in Shanghai. GRAPHICAL ABSTRACT: